Mary Amanda Dixon Jones papers - Dixon Jones, Mary Amanda
Correspondence, lectures, writings, notes, family papers, legal papers, financial papers, newspaper clippings, printed material, medical illustrations, photographs, and other papers relating primarily to Dixon Jones's career as a physician and surgeon, her legal difficulties, and her research and writings about diseases of the reproductive system. Subjects include her work as chief medical officer (1882-1884) and gynecologist (1884-1891) at the Woman's Hospital of Brooklyn, criminal lawsuits against Dixon Jones for the deaths of two patients and her lawsuit for libel against the Brooklyn Daily Eagle, and the murder of her daughter Mary D. Jones and death of her son Henry D. Jones. Family papers include correspondence, a patient logbook of her son Charles N. Dixon Jones, also a physician; a travel journal of her daughter Mary when she studied music in Europe in 1884; and a notebook with genealogical material about the Dixon family. Correspondents include Charles N. Dixon Jones, Henry D. Jones, and Mary D. Jones.
Library of Congress Rare Book and Special Collections Division.
Physician. Born 1828. Death date uncertain; Dixon Jones is listed as alive in the 1910 census.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dixon Jones, Mary Amanda -- Trials, litigation, etc; Jones, Charles N. Dixon; Jones, Charles N. Dixon -- Correspondence; Jones, Henry D; Jones, Henry D. -- Correspondence; Jones, Mary D; Jones, Mary D. -- -1893 -- Correspondence; Dixon family; Woman's Hospital of Brooklyn; Brooklyn daily eagle; Generative organs, Female -- Diseases; Gynecology -- New York (State) -- New York; Hospitals -- New York (State) -- New York; Libel and slander -- United States; Medicine -- New York (State) -- New York; Music -- Instruction and study -- Europe; Physicians -- Malpractice -- United States; Surgery -- New York (State) -- New York; Europe -- Description and travel; Physicians